Environmental Protection To Mitigate The Annual Forest And Land Fires Crisis In Riau Province Indonesia - Rd. Siti Sofro Sidiq; R. Yogie Prawira W (International Journal on Social Science, Economics and Art, 2019)
The crisis of haze in Riau Province Indonesia, due to the annual forest and land fires, has caused several problems in some countries across South East Asia including environmental law violation, air pollution, and health problems. Although continuous protests have been expressed by the local society and neighbouring countries, but the crisis seems still far away to be solved. Therefore, this study is aimed to offer a human right based approach to bridge the gap in mitigating the annual forest and land fires in Riau Province Indonesia. The type of the study is a desk research in which the writer examines the human based approach by using the perspective of environmental communication strategy. The result shows that human right based approach can be used as an environmental protection to mitigate the annual forest and land fires through environmental communication by maximizing the main elements of community participation such as holding events, campaigning hashtag movement, and giving penalties for companies which are involved in the forest and land burning crisis.